2012
DOI: 10.1177/030006051204000539
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Thoracoscopic Thymectomy for Thymoma without Myasthenia Gravis

Abstract: follow-up. Durations of chest intubation and hospitalization were significantly shorter in Group T than in Group S. No significant between-group difference in the incidence of operative complications was observed. Tumour recurrence-free rates at 5 and 7 years postsurgery were 96% (both years) in Group T and 95% (both years) in Group S. CONCLUSIONS: Long-term follow-up indicates that thoracoscopic thymectomy for thymoma without myasthenia gravis is effective and is well tolerated, and associated with low rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
2
4
1
2
Order By: Relevance
“…5 However, several recent studies reported survival and recurrence data for up to 10 years after VATS thymectomy. [20][21][22] 22 In this study, we reviewed our 13-year experience of the surgical treatment of stage I and II thymoma, and found similar outcomes to those reported in larger series. 20,21 The intermediate-term oncologic outcomes were as favorable as the outcomes after open thymectomy, supporting the feasibility of VATS thymectomy for the treatment of noninvasive thymoma.…”
Section: Discussion Oncologic Outcomessupporting
confidence: 64%
“…5 However, several recent studies reported survival and recurrence data for up to 10 years after VATS thymectomy. [20][21][22] 22 In this study, we reviewed our 13-year experience of the surgical treatment of stage I and II thymoma, and found similar outcomes to those reported in larger series. 20,21 The intermediate-term oncologic outcomes were as favorable as the outcomes after open thymectomy, supporting the feasibility of VATS thymectomy for the treatment of noninvasive thymoma.…”
Section: Discussion Oncologic Outcomessupporting
confidence: 64%
“…[14][15][16] Several recent studies have reported recurrence and survival data up to 7 years after VATS thymectomy and conclude that recurrence-free and overall survivals are similar to those after open thymectomy. 6,[24][25][26] While we recognize that most recurrent disease occurs within 5 to 10 years of the primary resection, we did assess factors that may be surrogate measures of oncologic efficacy, which may affect long-term oncologic outcomes. These included R0/R1 resection, extent of thymectomy, ability to resect involved structures and adjuvant radiation therapy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Using the modified Masaoka staging system, Agasthian and colleagues 10 suggested that early-stage thymomas can be safely resected with VATS; but 13 invasive thymomas were also successfully resected with VATS, with modifications in the technique, without resorting to sternotomy. A study by Chung and colleagues 11 on 25 patients undergoing thoracoscopic thymectomy for thymoma without MG, showed that none of the patients had Masaoka stage III, and only one had Masaoka stage IV disease. Similarly, our data showed that only 2 (3.8%) thymomas were stage III.…”
Section: Discussionmentioning
confidence: 99%